Quantificação da organização e arquitetura do colágeno em queimaduras cutâneas por meio da dimensão fractal, lacunaridade e transformada rápida de Fourier - Rocha, José Lima de Carvalho (2022)
The scope of the treatment of burns extends beyond the preservation of life and function, seeking to allow the survivors the return to feeling productive and fully accepted in their communities. The healing / repair of a burn, The healing / repair of a burn, when undergoing uncontrolled infection, chronic inflammation, foreign body reactions or innate tendency to fibrosis or hyper healing may result in keloids, flangesand / or hypertrophic scars. Collagen makes up 80% of the papillary dermis and almost 90% of the reticular dermis, being most largely responsible for the mechanical and physical properties of the skin. It is possible to assume that post-burn integument changes are due to changes in the organization, microstructure, orientation and collagen texture. In the biomedical field, the Fractal Dimension and lacunarity have been used in research on the growth pattern and neuronal plasticity and glial cells,cancer cells, static and dynamic analysis of renal and pulmonary vasculature,quantification of cardiac transplantation rejection, quantifying cirrhosis and fibroticdamage on periprosthesis silicone capsules, among other applications. The objectives of this thesis were to evaluate quantitatively by means of an image analyzer program, Fractal Dimension, Lacunarity and the pattern of deposition ofncollagen type I and type III in the skin of mice subjected to partial thickness burns, treated or not with bleomycin also measuring the architectural organization of these collagen fibers through the Fast Fourier Transform. The fractal dimension was able to effectively differentiate burns treated with saline or bleomycin from those of healthy skin. The values of fractal dimension in the bleomycin group were approaching the values found in normal skin. The lacunarity of collagen type III was higher during the proliferative phase and also at the end of the healing process in the bleomycin group,which shows a dual action of this substance in the modulation of the proliferation and the collagen remodeling. The orientation of the collagen fibers presented values closer to those of the intact skin in the group treated with saline. Bleomycin has been able to significantly change the reorientation of collagen fibers at the end of the repair process. Keywords: Burns, collagen,